2020
DOI: 10.1002/ajoc.201900680
|View full text |Cite
|
Sign up to set email alerts
|

Thioamidation of Arylpropyne Derivatives with Sulfur and Formamides for the Synthesis of Aryl Propanethioamides

Abstract: An efficient synthesis of aryl propanethioamides by a three-component reaction of arylpropynes, elemental sulfur and formamides has been developed. The cascade thioami-dation proceeds smoothly through the hydrolysis of the CÀ C triple bond and formamides, the formation of CÀ N bond and CÀ S double bond in one-pot reaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 64 publications
0
2
0
Order By: Relevance
“…Control experiments indicated that the cleavage of the C=C bond produced formaldehyde, which was further oxidized to formic acid. Formamides can also be used in place of amines, such as in the 2020 work reported by Zhang's group [46] on the three-component reaction of arylpropynes 61, formamides, and elemental sulfur (Scheme 24). The KF-mediated reaction led efficiently to the targeted aryl propanethioamides 62 with wide structural scope.…”
Section: Thionylation Of Alkynes and Alkenesmentioning
confidence: 99%
See 1 more Smart Citation
“…Control experiments indicated that the cleavage of the C=C bond produced formaldehyde, which was further oxidized to formic acid. Formamides can also be used in place of amines, such as in the 2020 work reported by Zhang's group [46] on the three-component reaction of arylpropynes 61, formamides, and elemental sulfur (Scheme 24). The KF-mediated reaction led efficiently to the targeted aryl propanethioamides 62 with wide structural scope.…”
Section: Thionylation Of Alkynes and Alkenesmentioning
confidence: 99%
“…Aryl propanethioamides 62 could be obtained from internal alkynes by this transformation, indicating that this process shared some similarities with the Willgerodt rearrangement. Formamides can also be used in place of amines, such as in the 2020 work reported by Zhang's group [46] on the three-component reaction of arylpropynes 61, formamides, and elemental sulfur (Scheme 24). The KF-mediated reaction led efficiently to the targeted aryl propanethioamides 62 with wide structural scope.…”
Section: Thionylation Of Alkynes and Alkenesmentioning
confidence: 99%